The Effect of Temperature Variation on the Liquefaction of High-Density Polyethylene Plastic Waste - Alfernando, Oki; Marpaung, Gabriel Adi Pratama (Universitas Trunojoyo Madura, 2024)
This study aims to determine the comparison of oil yields obtained from processing HDPE plastic waste by comparing quantitatively and qualitatively the fuel oil produced. The processing of plastic waste into oil by pyrolysis process was carried out at a temperature variation of (400; 500; 600; 700; 800)°C for 120 minutes. In one experiment, 500 grams of plastic waste, 250 grams of dolomite catalyst, and 250 ml of H2SO4 solvent were required. This research was conducted at the Laboratory of SKL Engineering Department, Jambi University with the parameters tested including volume, mass, %-yield, density, and GC-MS analysis. The results showed that quantitatively the lowest volume, mass, and %-yield were at the 400oC temperature variation, and the highest at 500oC. At 500oC pyrolysis temperature variation, the resulting density was 0.744 grams/ml, and the results of GC-MS analysis produced carbon chains C5-C12 97.6081% (gasoline), C13 2.3919% (kerosene), and aromatic compounds contained in it amounted to 14.3786%.